Tuesday

September 23, 2014

September 23, 2014

Posted by **shyam** on Sunday, June 23, 2013 at 1:55am.

- maths -
**MathMate**, Sunday, June 23, 2013 at 6:23amAssume the equation has three roots a,b and c:

then

(x-a)(x-b)(x-c)=0

x³-(a+b+c)x²+(ab+bc+ca)x-abc=0

which means

(a+b+c)=-3 (negative of coeff.of x²)

(ab+bc+ca)=-7 (coeff. of x)

Hence

a²+b²+c²

=(a+b+c)²-2(ab+bc+ca)

=3²-2(-7)

=9-(-14)

=23

**Answer this Question**

**Related Questions**

math - Find the sum of the squares of the three solutions of the equation x^3+3x...

Maths - What is the sum of all real solutions to the equation x−6/4=−...

Math - Find the augmented matrix for each of the following systems of linear ...

calc - Find an equation of the tangent line to the graph of f(x) = (x3 − ...

Math (Algebra) - Find the sum of squares of all real roots of the polynomial f(x...

maths - Let's denote the three numbers by a1, a2, and a3. Consider the third ...

MATHS - Find the number of real solutions of the system of equations. x^2−...

Maths - The sum of the squares of three consecutive positive integers is 365 ...

Maths - Is (0, 3) a solution to the equation y = x + 3? I think yes. Is (1, &#...

Calc. - I am so confused with this last part of the unit! What in the world is ...